Soil properties and climate mediate the effects of biotic interactions on the performance of a woody range expander. Issue 4 (17th April 2018) - Tomiolo, Sara; Ward, David
Abstract: Expansion of trees into grasslands and old fields is a complex process that leads to a decline of biodiversity and reduces rangeland availability. Climate and land‐use change contribute to accelerated rates of range expansion. However, the role of biotic interactions in promoting or hindering woody range expanders is still unclear. We investigated the combined effects of abiotic (soil properties and climate) and biotic (simulated grazing and intra‐ and interspecific plant–plant interactions) factors on a woody range‐expander, Juniperus virginiana, which has been spreading into grasslands and old‐field habitats in North America. We hypothesized that interspecific competition would negatively affect growth and survival of J. virginiana due to belowground competition with herbaceous species; grazing would favor J. virginiana via competitive release, and intraspecific interactions would be beneficial to tree seedlings during early life stages by means of facilitation. We also predicted that a thicker winter snowpack would have a positive impact on tree growth by providing protection from frost damage. In a multisite field experiment, we exposed J. virginiana seedlings to intra‐ and interspecific interactions, as well as simulated grazing of surrounding herbaceous species. These treatments were repeated at three different sites that vary in soil properties and that are situated along a precipitation gradient. Additionally, we conducted a snow‐manipulation experiment at one of the sites. We conducted our monitoring for two consecutive growing seasons characterized by very different rainfall conditions, the second growing season receiving between 6% and 14% more rainfall than the first. Under lower rainfall availability, interspecific interactions between tree seedlings and herbaceous species negatively affected seedling growth rates. However, this effect was detectable only during the drier year and at the site characterized by more favorable soil properties. During winter, we found that deeper snow cover was associated with decreased growth rate of plants, probably due to repeated freeze‐thaw cycles. Our results indicate that the role of biotic interactions had an effect only under harsh climatic conditions and that abiotic factors may affect range expansion directly and indirectly via biotic interactions.